A CASE OF APPENDECTOMY OF CONGENITAL FACTOR XI DEFICIENCY - SASAKI, Hideaki (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 1999)
This paper presents a case of congenital factor XI deficiency which was clarified by prominent prolongation of APTT in preoperative examination for acute appendicitis, as well as a study of the patient's family. A 48-year-old man after diagnosed as having appendicitis was referred to the hospital by a small island clinic. Preoperative evaluation showed marked prolongation of APTT (127.0 second with a standard of 29.6 sec.). When using a 1:1 mixture of the patient and normal plasma, the prolongation of APTT was normalized. An appendectomy was successfully performed. Any transfusion of fresh frozen plasma was not required. The patient revealed no bleeding tendency during hospitalization, but postoperative evaluation indicated that his factor XI was less than 3%. Several months later, his son, who also underwent an appendectomy for appendicitis, was found to have a prolonged APTT of 38.3 sec. (31.0 sec.), and a factor XI of 36%. His daughter, who had undergone a cervical spine surgery for Morquio's disease, had a prolonged APTT of 35.8 sec. (30.4 sec.) and a factor XI of 35%. His wife had normal coagulation tests. These facts suggest that the patient has homozygous and his children heterozygous factor XI deficiency.